Hot or not: the influence of elevated temperature and microwave irradiation on the solid phase synthesis of an affibody - Nissen, Felix; Kraft, Thomas E.; Ruppert, Thomas; Eisenhut, Michael; Haberkorn, Uwe; Mier, Walter (Tetrahedron letters, 2010)
Despite the advances of solid phase peptide synthesis (SPPS) the synthesis of long peptides is still challenging. Microwave irradiation and conventional heating are considered to improve the efficiency of SPPS. It has been shown that conventional heating and heating by microwave irradiation improves the efficiency of solid phase synthesis of peptides that are prone to aggregation as compared to the synthesis at room temperature. In this Letter, the influence of elevated temperature and microwave irradiation on the homogeneity of the synthesis product of a 58-mer peptide affibody has been compared. A detailed analysis by high resolution HPLC and LC-MS mass spectrometry using a high-mass resolution Orbitrap Exactive mass spectrometer was performed. This study revealed that neither thermal heating nor microwave heating improves the yield and purity of the crude product as compared to the synthesis at room temperature. In contrast, the formation of undesirable side products rather increased by microwave irradiation. These results indicate that neither heating nor microwave enhancement of solid phase synthesis does allow a significant improvement of peptide sequences with a low aggregation potential.